PENDEKATAN TARL UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA DI SDN TAENG - Ulviani, Maria (Program Studi Magister Pendidikan Bahasa dan Sastra Indonesia, Program Pascasarjana, Universitas Pasundan Bandung, 2025)
This study aims to determine the effect of the Teaching at the Right Level (TaRL) approach in improving the Indonesian language learning outcomes of fourth-grade students at SDN Taeng. The TaRL approach enables student grouping based on their abilities, allowing instruction to be tailored to their comprehension levels. This research was conducted in two cycles using the classroom action research (CAR) method. The results indicate that the learning mastery level in the pre-cycle was only 44%, increased to 67% in Cycle I, and reached 85% in Cycle II. These findings demonstrate that the TaRL approach is effective in enhancing student learning outcomes. The implication of this study is that the TaRL approach can serve as an alternative strategy to improve the quality of Indonesian language learning, emphasizing student grouping according to their initial abilities.